Effect of frame foundation geometry on the dynamic response of high-speed turbo machine foundations - Ameer A. Ahmed; Mohammed Y. Fattah; Makki K. Mohsen (Heliyon)
The foundation of the turbo-generator comprises a generator, turbine, and associated equipment situated on the top of the frame foundation, which consists of a bottom raft, top deck, and columns. The current study examines how the geometrical characteristics of the frame foundation, such as slab thickness, column dimensions, and length, affect the dynamic displacement response and the natural frequencies of the frame foundation. The work is done through 3-D dynamic modal and harmonic analyses using Ansys Workbench finite element software. The impact of the top deck thickness was investigated using five thicknesses of (1.0, 1.2, 1.4, 1.6 and 1.8) m. To inspect the effect of the column's dimensions, the column's length was fixed for all cases, other frame dimensions are based on the prototype dimensions. The columns were assumed to be square with dimensions of (0.8, 0.9, 1.0, 1.1 and 1.2) m. The prototype slab, raft, and column dimensions are adopted for all cases to inspect the effect of the column's length. The column lengths of (6.8, 7.8, 8.8, 9.8, and 10.8) m were used to examine the column length effect on the frame foundation.The study's results revealed that decreasing column length or increasing column dimensions increases the frame foundation's natural frequencies, and the frame's displacement response decreases remarkably. The results also revealed that changing the tabletop slab thickness has a marginal effect on the frame's dynamic performance. The results show that the behavior for different geometrical frame foundations can be presented by a single normalized curve for frame foundation.